Self-Evaluation of the Faculty of Sciences of Engineering and Technology UABC According to UI Green Metric 2023 - Maria Cristina Castañon Bautista; Alicia Ravelo Garcia; Juan Antonio Pitones Rubio (Journal of Sustainability Perspectives, 2025)
The objective of this study is to use the Guideline UI GreenMetric World University Rankings 2023 guide, with the purpose of evaluating the sustainability performance of the Faculty of Sciences of Engineering and Technology (FCITEC) Valle de Las Palmas Academic Unit of the Autonomous University of Baja California (UABC). According to the available documentary information from years 2020 to 2023 of the annual activity reports of the faculty’s Dean, in addition to statistical data and Study Plan documents of the Educational Programs offered at FCITEC, as well as activity reports of environmental management, all published on the institutional website, which are used to evaluate according to the six categories of the UI GreenMetric 2023; with the intention of generating a baseline to help propose actions and strategies for continuous improvement for the benefit of the university community, as well as the local environment and community. With the self-assessment, the findings of compliance with the categories were between 27% and 75%, where the highest global average corresponds to waste management and the lowest for transportation. Continuous work and improvement is necessary to achieve the sustainable performance of FCITEC, so that it can comply with the UI GreenMetric standards, in a way in which the academic unit can reduce negative environmental impacts in its surroundings.